The Acute-Phase Proteins Serum Amyloid A and C Reactive Protein in Transudates and Exudates - Alessandra M. Okino; Cristiani Bürger; Jefferson R. Cardoso; Edson L. Lavado; Paulo A. Lotufo; Ana Campa (Hindawi Limited, 2006)
The distinction between exudates and transudates is very important in the patient management. Here we evaluate whether the acute-phase protein serum amyloid A (SAA), in comparison with C reactive protein (CRP) and total protein (TP), can be useful in this discrimination. CRP, SAA, and TP were determined in 36 exudate samples (27 pleural and 9 ascitic) and in 12 transudates (9 pleural and 3 ascitic). CRP, SAA, and TP were measured. SAA present in the exudate corresponded to 10% of the amount found in serum, that is, the exudate/serum ratio (E/S) was 0.10±0.13. For comparison, the exudate/serum ratio for CRP and TP was 0.39±0.37 and 0.68±0.15, respectively. There was a strong positive correlation between serum and exudate SAA concentration (r=0.764;p<0.0001). The concentration of SAA in transudates was low and did not overlap with that found in exudates (0.02-0.21 versus 0.8-360.5 g/mL). SAA in pleural and ascitic exudates results mainly from leakage of the serum protein via the inflamed membrane. A comparison of the E/S ratio of SAA and CRP points SAA as a very good marker in discriminating between exudates and transudates